Effects of some channelling agents on the compaction properties of the mixed stem bark extracts of Anogeissus leiocarpus and Prosopis africana - Emeje Martins; Isimi Christianah; Izuka Amaka; Olayemi Olubunmi (Islamic Azad University, Shahrekord Branch, 2017)
Background & Aim: The hot water extract of a mixture of Anogeissus leiocarpus and Prosopis africana is widely used in the northern part of Nigeria for the treatment and management of asthma. Since investigations of its pharmacological activities already justify its use, and the need for standardization of herbal medicine and develop appropriate dosage forms has continued to grow, the purpose of this study was to evaluate the effects of some common channelling agents (sodium bicarbonate, calcium carbonate and sodium lauryl sulphate) on the compaction properties of the mixed stem bark extracts of Anogeissus leiocarpus and Prosopis africana. Experimental: Granules of the mixed extracts (AA1) were produced using the wet granulation method of massing and screening. The micromeritics and flow properties of the extracts as well as the effects of the three common additives were studied, while the compaction properties of the extract formulated alone and in the presence of these additives were interrogated using the Heckel equation. Results: Our results showed that, all the formulations containing the channelling agents exhibited poor flow. Granules prepared using sodium bicarbonate (NaHCO3) exhibited plastic deformation during consolidation, those formulated using calcium carbonate (CaCO3) showed initial fragmentation before consolidation by plastic deformation and those formulated using sodium lauryl sulphate consolidated essentially by plastic deformation. Inclusion of additives modified the compressibility profiles of the formulations. Tensile strength of the formulations containing NaHCO3 and sodium lauryl sulphate (SLS) were observed to be concentration dependent while those containing CaCO3 showed no appreciable increase in tensile strength with increased pressure. Generally, formulations containing 5% of the additives gave the highest tensile strength, however, those containing CaCO3 were found to be higher than the other two formulations. Recommended applications/industries: Considering that, none of the channelling agents altered significantly the compaction properties of AA1, they might be useful in developing standardized and robust tablets of A. leiocarpus and P. africana admixtures for Asthma therapy.